2000
DOI: 10.1139/o00-017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular correlates of the action of bis(ethyl)polyamines in breast cancer cell growth inhibition and apoptosis

Abstract: Polyamines are known to be involved in cell growth regulation in breast cancer. To evaluate the efficacy of bis(ethyl)polyamine analogs for breast cancer therapy and to understand their mechanism of action we measured the effects of a series of polyamine analogs on cell growth, activities of enzymes involved in polyamine metabolism, intracellular polyamine levels, and the uptake of putrescine and spermidine using MCF-7 breast cancer cells. The IC50values for cell growth inhibition of three of the compounds, N1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Previous studies by us and other investigators have shown a delayed apoptotic response by polyamine analogs in several cancer cell lines (Faaland et al, 2000;Kramer et al, 1997). Therefore, we performed experiments after 72 and 96 h of treatment with polyamine analogs.…”
Section: Effect Of Polyamine Analogs On Nf-kb Translocation and Apoptmentioning
confidence: 73%
See 4 more Smart Citations
“…Previous studies by us and other investigators have shown a delayed apoptotic response by polyamine analogs in several cancer cell lines (Faaland et al, 2000;Kramer et al, 1997). Therefore, we performed experiments after 72 and 96 h of treatment with polyamine analogs.…”
Section: Effect Of Polyamine Analogs On Nf-kb Translocation and Apoptmentioning
confidence: 73%
“…Thus, these polyamine analogs were active in inhibiting both ERE-and NRE-promoters, with some structure-dependent di erences in their e cacy. Previous studies from our laboratory and others have shown that these polyamine analogs inhibit cell growth and induce apoptosis over the course of 2 ± 4 days (Davidson et al, 1993;Faaland et al, 2000;Hu and Pegg, 1997). Thus inhibition of transactivation observed at 24 h preceded e ects on cell growth or cell death.…”
Section: Effect Of Polyamine Analogs On Ere-and Nre-mediated Gene Tramentioning
confidence: 78%
See 3 more Smart Citations